PENGELOLAAN SANGGAR KEGIATAN BELAJAR (SKB) PADA ERA OTONOMI DAERAH - Widodo Widodo (Universitas Negeri Yogyakarta, 2015)
This study aimed to describe the management implementation of Learning Activities Gallery (LAG) in the autonomy era. Description of Non-formal Education program management, Human Resources management, and financial management. Its purpose is able to create (1) facilities and able to bridge regions to the center, (2) the emergence of creativity in the construc-tion area, (3) political stability and regional centers, (4) the assurance of business continuity, and (5) open communication. But in fact the management of LAG was facing problems regarding the amount of funding that was not sufficient, human resources was not professional, and the prog-ram did not develop. Research used qualitative case studies approach of various problems in some LAG. Then dialogic analyzed by Milles and Huberman included; data collection, data reduc-tion, data display and conclusions. The study found that LAG management in the autonomy era, there was already successful and the support of the local government, but most of the LAG was not growing even threatened dissolved or merged. LAG institutional management were not well developed caused by the lack of professional Human Resources, the lack of funding support. So from some of these problems were concluded that LAG management in the era of regional auto-nomy had a tendency to decrease or even unprofessional. Regional autonomy must consider LAG as a unit organizer non-formal and informal education programs with the full support of the government both funds and human resources professionals.